Solar Cell Manufacturing Cost Analysis and its Impact to Solar Power Electricity Price in Indonesia - Hermawan, Erwan; Wijono, Raden Agung; Adiarso, Adiarso; Setiyadi, Ermawan Darma; Hadiyati, Nur Anis; Setiadi, Sigit; Setiawan, Hari; Ferabianie, Ayu Lydi; Dewi, Yanti Rayana; Fatmakartika, Ontin (International Journal of Energy Economics and Policy, 2023)
World energy consumption continues to increase, with a growth of 1,3% annually during 2011 - 2021. To deal with that situation, in 2021, Indonesia Electrity Stated-Own Company (PLN) issued a report about the electricity supply business plan (RUPTL) 2021-2030. The power plant projected to grow is solar photovoltaic (PV), reaching 4,6 GW within ten years. However, in reality, the achievement of developing solar power plants is still 0,02 GW. Several factors that caused low realization are the solar power plant component industry needs to be better developed, and the regulated electricity price based on Presidential Decree 112/2022 needs to be increased. This study aims to determine the cost structure of solar module manufacturing and the impact on electricity prices. The calculation method used is financial modeling with economic parameters such as Internal Rate of Return (IRR), payback period, and Net Present Value (NPV) as parameters for project feasibility. The results of this study show that the economic price of solar power plants in Indonesia is USD 0,149/kWh. Meanwhile, based on a sensitivity analysis using electricity prices based on Presidential Decree, reducing solar module costs up to 50% still does not make the project feasible.